Dot Product
Geometric Definition
Let $\vec v \cdot \vec w$ denote the dot product between vectors $\vec v$ and $\vec w$
- definition: $\vec v \cdot \vec w = \| \vec v \| \cdot \| \vec w \| \cdot \cos \theta$ where $\theta$ is the angle between $\vec v$ and $\vec w$
- $\| \vec v \|$ denotes the length of $\vec v$
- if two vectors are perpendicular, then $\cos \theta = 0$ and thus $\vec v \cdot \vec w = 0$
- if they co-directional, then $\theta = 0$ and $\vec v \cdot \vec w = \| \vec v \| \cdot \| \vec w \|$
- consequently, we have $\vec v \cdot \vec v = \| \vec v \|^2$
Projections
Dot product is a projection:
- let's project $\vec v$ onto $\vec w$: $\text{proj}_{\vec w} (\vec v) = \| \vec v \| \cos \theta$ (by the $\cos$ definition)
- we're interested only in the direction of $\vec w$, so let's normalize it to get $\hat w = \vec w / \| \vec w \|$ - it's the unit vector in the direction $\vec w$
- $\vec v \cdot \hat w$ - dot product of $\vec v$ and some unit vector
- $\vec v \cdot \hat w = \| \hat w \| \| \vec v \| \cos \theta = \| \vec v \| \cos \theta$
- it is a projection in the direction of $\vec w$
- so $\vec v \cdot \hat w$ corresponds to the projection of $\vec v$ onto $\vec w$
- $\text{proj}_{\vec w} (\vec v) = \vec v \cdot \hat w = \| \vec v \| \cos \theta$ - is the length of this projection
- thus, $\vec v \cdot \vec w = \| \vec v \| \| \vec w \| \cos \theta = \| \vec w \| \cdot \text{proj}_{\vec w} (\vec v) = \| \vec v \| \cdot \text{proj}_{\vec v} (\vec w)$
$p = \text{proj}_{\vec u} (\vec v) = \vec v \cdot \hat u = \| \vec v \| \cos \theta$
- it can be positive or negative
- positive when angle between vectors is less than $90^o$
- negative when angle between vectors is greater than $90^o$
The Cosine Theorem
Why does this geometric definition make sense?
- consider vectors $\vec u$, $\vec v$ and $\vec w$
- let $\vec v + \vec u = \vec w$ or $\vec u = \vec w - \vec v$
-
- $\| \vec u \|^2 = \| \vec w - \vec v \|^2 = (\vec w - \vec v) \cdot (\vec w - \vec v) = \| \vec w \|^2 + \| \vec v \|^2 - 2 \cdot \vec w \vec v$
- by the Cosine Theorem we know that
- $\| \vec u \|^2 = \| \vec w - \vec v \|^2 = \| \vec w \|^2 + \| \vec v \|^2 - 2 \cdot \| \vec w \| \cdot \| \vec v \| \cdot \cos \theta$
- so $\| \vec w \| \cdot \| \vec v \| \cdot \cos \theta = \cfrac{1}{2} (\| \vec w \|^2 + \| \vec v \|^2 - \| \vec w - \vec v \|^2) = \cfrac{1}{2} (\| \vec w \|^2 + \| \vec v \|^2 - \| \vec w \|^2 - \| \vec v \|^2 + 2 \cdot \vec w \vec v) = \vec w \cdot \vec v$
- thus $\vec w \cdot \vec v = \| \vec w \| \cdot \| \vec v \| \cdot \cos \theta$
- i.e. the definition makes sense from the The Cosine Theorem point of view
Algebraic Definition
For two vectors $\mathbf v, \mathbf w \in \mathbb R^n$ we define the dot product as $\mathbf v^T \mathbf w = \sum\limits_{i = 1}^n v_i w_i$
$\mathbf v \; \bot \; \mathbf w \iff \mathbf v^T \mathbf w = 0$
Why?
- by the Pythagoras theorem: $\| \mathbf v \|^2 + \| \mathbf w \|^2 = \| \mathbf v + \mathbf w \|^2$
- $\mathbf v^T \mathbf v + \mathbf w^T \mathbf w = (\mathbf v + \mathbf w)^T (\mathbf v + \mathbf w) = \mathbf v^T \mathbf v + \mathbf v^T \mathbf w + \mathbf w^T \mathbf v + \mathbf w^T \mathbf w$
- or $\mathbf v^T \mathbf w + \mathbf w^T \mathbf v = 0$
- note that $\mathbf v^T \mathbf w = \mathbf w^T \mathbf v$, so we have
- $2 \mathbf v^T \mathbf w = 0$ or $\mathbf v^T \mathbf w = 0$
Equivalence of Definitions
Both definitions are equivalent.
I.e. $\vec v \cdot \vec w = \mathbf v^T \mathbf w = \| \vec v \| \| \vec w \| \cos \theta = \sum\limits_{i = 1}^n v_i w_i$
Why?
- let $\vec e_1, \ ... \ , \vec e_n$ be the standard basis in $\mathbb R^n$
- these vectors are orthonormal, i.e. $\vec e_i \cdot \vec e_j = \begin{cases}
1 & \text{if } i = j \\
0 & \text{if } i \ne j \\
\end{cases}$
- let's consider a dot product $\vec v \cdot \vec e_i$: $\vec v \cdot \vec e_i = \| \vec v \| \cos \theta = v_i$ - it's a projection of $\vec v$ onto $ \vec e_i$ - which is $i$th component of $\vec v$
- we can project $\vec v$ and $\vec w$ onto the entire basis and get
- $\vec v = \sum\limits_{i = 1}^n v_i \cdot \vec e_i$ and $\vec w = \sum\limits_{i = 1}^n w_i \cdot \vec e_i$
- So, $\vec v \cdot \vec w = \vec v \cdot \sum\limits_{i = 1}^n w_i \vec e_i = \sum\limits_{i = 1}^n w_i (\vec v \cdot \vec e_i) = \sum\limits_{i = 1}^n v_i w_i$
$\square$
Sources